PENGARUH PROFITABILITAS, STRUKTUR AKTIVA, LIKUIDITAS DAN RASIO UTANG TERHADAP STRUKTUR MODAL PADA PERUSAHAAN FARMASI DI BEI - Riska Wulandari, Anita Wijayanti & Endang Masitoh W (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
This research was conducted aiming to find out the influence of the structure of assets, profitability, liquidity and capital structure debt ratios on pharmaceutical companies in BEI 2013 - 2017 period. This research is quantitative research are causal associative. Samples were taken using a purposive sampling technique. Sample company used in this study as many as 7 companies in 5 periods of as much as 35, while there are outlier data is 1, so the sample research as much as 34 samples. Data analysis techniques used are descriptive statistics, test the assumptions of linear multiple regression, classic and test hypotheses as well as the process of using SPSS 23. The results showed that (1) the profitability of influential positive but insignificant, indicated by the coefficient of regression of 0.176 and significance of 0.515 (2) the structure of assets of influential positive but not significant indicated by the coefficient of regression 0.078 and significance of 0.470 (3) Liquidity the positive and significant effect was demonstrated with regression coefficients of 0.054 and significance of 0.000 (4) positive and influential debt Ratio significant regression coefficient indicated by registration of 3.094 and significance of 0.000. So it can be inferred the profitability and structure of the assets has no effect to the structure of capital, liquidity and debt ratios whereas the effect on capital structure. Keywords: profitability, structure of assets, liquidity, debt ratio, capital structure